Green synthesis of silver nanoparticles using Rheum palmatum root extract and their antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa. (17th February 2017) - Arokiyaraj, Selvaraj; Vincent, Savariar; Saravanan, Muthupandian; Lee, Yoonseok; Oh, Young Kyoon; Kim, Kyoung Hoon
Abstract: In the present study, silver nanoparticles (AgNPs) were synthesized by using aqueous root extracts of Rheum palmatum and characterized by various spectroscopic methods. The nanoparticles were found to be in hexagonal and spherical shapes. The average particle size was found to be 121 ± 2 nm with zeta potential values of −21.6 mv by dynamic light scattering (DLS) method. Gas chromatography–mass spectrometry (GC-MS) analysis of R. palmatum revealed 35 compounds. The synthesized AgNPs showed significant activity against Staphylococcus aureus and Pseudomonas aeruginosa with IC90 values of 15 μg/ml and IC50 values of 7.5 μg/ml, respectively. The protein leakage level was high and morphological changes occurred in bacteria treated with AgNPs.